Novel hKDR mouse model depicts the antiangiogenesis and apoptosis‐promoting effects of neutralizing antibodies targeting vascular endothelial growth factor receptor 2. Issue 1 (10th October 2022) - Cao, Yuan; Sun, Chunyun; Huo, Guitao; Wang, Huiyu; Wu, Yong; Wang, Fei; Liu, Susu; Zhai, Shijie; Zhang, Xiao; Zhao, Haoyang; Hu, Meiling; Gu, Wenda; et al.
Abstract: Vascular endothelial growth factor receptor 2 (VEGFR2)/KDR plays a critical role in tumor growth, diffusion, and invasion. The amino acid sequence homology of KDR between mouse and human in the VEGF ligand‐binding domain was low, thus the WT mice could not be used to evaluate Abs against human KDR, and the lack of a suitable mouse model hindered both basic research and drug developments. Using the CRISPR/Cas9 technique, we successfully inserted different fragments of the human KDR coding sequence into the chromosomal mouse Kdr exon 4 locus to obtain an hKDR humanized mouse that can be used to evaluate the marketed Ab ramucirumab. In addition, the humanized mAb VEGFR‐HK19 was developed, and a series of comparative assays with ramucirumab as the benchmark revealed that VEGFR‐HK19 has higher affinity and superior antiproliferation activity. Moreover, VEGFR‐HK19 selectively inhibited tumor growth in the hKDR mouse model but not in WT mice. The most important binding epitopes of VEGFR2‐HK19 are D257, L313, and T315, located in the VEGF binding region. Therefore, the VEGFR2‐HK19 Ab inhibits tumor growth by blocking VEGF‐induced angiogenesis, inflammation, and promoting apoptosis. To our best knowledge, this novel humanized KDR mouse fills the gaps both in an animal model and the suitable in vivo evaluation method for developing antiangiogenesis therapies in the future, and the newly established humanized Ab is expected to be a drug candidate possibly benefitting tumor patients. Abstract : We successfully inserted human KDR CDS into the chromosomal mouse Kdr to obtain an hKDR humanized mouse using CRISPR/Cas9 technique, and V135I, L313R, I266L sites are different ligand‐binding regions of VEGFR2 between humans and mice. Bottom line: DC101, targeting mouse VEGFR2, does not cross‐react with human VEGFR2, is evaluated in WT xenograft tumor mice, showing that the tumor volume is reduced obviously. Ramucirumab, a humanized IgG1 monoclonal antibody ramucirumab (IMC‐1121B, product name: CYRAMZA®), is evaluated in hKDR and WT xenograft tumor mice respectively, showing that the tumor volume is reduced obviously in hKDR mice but not in WT mice, indicating that hKDR mice reproduced the activity of approved Ab in vivo. VEGFR‐HK19, a new humanized mAb, similar with ramucirumab, selectively inhibited tumor growth in the hKDR mouse model but not in WT mice, indicating that VEGFR2‐HK19 showed antitumor activity.